The Effect of Digital Transaction Effectiveness, Financial Inclusion and Customer Satisfaction on Company Profits - Nur Aisyah, Sitatul; Hapzi Ali (Dinasti Publisher, 2023)
Literature Review Article Effects of Digital Transaction Effectiveness, Financial Inclusion and Customer Satisfaction on Corporate Profits is a scientific article in the field of Financial Management which aims to analyze and synthesize the effect of each variable on research research originating from research or journals that are already in the media online such as Mendeley, Google Scholar, and several other websites. The literature that has been reviewed will be further studied to obtain research gaps and research novelties are found. This review article has 3 discussion results, namely; 1) Digital Transactions affect Company Profits 2) Financial Inclusion affects Company Profits ; and 3) Customer Satisfaction affects Company Profits.